Design, development and implementation of a voice email system using next generation networks technology - a case study - Rao, G.S.V.R.K.; Siew, E. (2005)
In very near future, as more and more companies start to build the Next Generation Networks for developing applications, it will give birth to more solutions and products for the needs of the market. The Voice Email system will definitely be one of them and it will soon become another trend for the technology savvy users. The Voice Email system will become a starting point for the future of voice browsing technologies over the phone where there will be wide spreading of applications and services from different areas, such as stock trading and voice conferencing.